(untitled) - Camilo Guzmán; Salim Mattar; Silvana Levis; Noemí Pini; Tadeu Figueiredo; James Mills; Jorge Salazar-Bravo (Memorias do Instituto Oswaldo Cruz, 2013)
We tested sera from 286 agricultural workers and 322 rodents in the department of Córdoba, northeastern Colombia, for antibodies against two hantaviruses. The sera were analysed by indirect ELISA using the lysate of Vero E6 cells infected with Maciel virus (MACV) or the N protein of Araraquara virus (ARAV) as antigens for the detection of antibodies against hantaviruses. Twenty-four human sera were IgG positive using one or both antigens. We detected anti-MACV IgG antibodies in 10 sera (3.5%) and anti-ARAV antibodies in 21 sera (7.34%). Of the 10 samples that were positive for MACV, seven (70%) were cross-reactive with ARAV; seven of the 21 ARAV-positive samples were cross-reactive with MACV. Using an ARAV IgM ELISA, two of the 24 human sera (8.4%) were positive. We captured 322 rodents, including 210 Cricetidae (181 Zygodontomys brevicauda, 28 Oligoryzomys fulvescens and 1 Oecomys trinitatis), six Heteromys anomalus (Heteromyidae), one Proechimys sp. (Echimyidae) and 105 Muridae (34 Rattus rattus and 71 Mus musculus). All rodent sera were negative for both antigens. The 8.4% detection rate of hantavirus antibodies in humans is much higher than previously found in serosurveys in North America, suggesting that rural agricultural workers in northeastern Colombia are frequently exposed to hantaviruses. Our results also indicate that tests conducted with South American hantavirus antigens could have predictive value and could represent a useful alternative for the diagnosis of hantavirus infection in Colombia.